Review On Innovative Flours to Increase The Nutritional Value And Organoleptic Acceptabi;ity of Food, Especially Cakes, Slices of Bread and Pizza - Nini, Rifni Novitasari; Tuty Anggraini; Hasbullah; Dini Hervani (Universitas Lancang Kuning, 2023)
Most cakes, breads, and other snacks are made from wheat flour. Using wheat flour as processed food is not suitable for health because wheat flour contains gluten. With the growing awareness of the importance of health, there have recently been many studies on innovative flour substitutes for wheat flour in food processing, which are rich in beneficial bioactive components. This innovative flour is used in particular types of bread and pizza. This study aims to study the effect of innovative flour on the physical, texture, taste, and nutritional properties of bread and pizza dough. In addition, this research can also describe steps to optimize dough formulations with innovative flours to achieve healthier, low-gluten dough. The method used in writing this scientific work results from a Systematic Literature Review (SLR) from published scientific journals, national and international journals. From the literature obtained, it was found that innovative potato-based flour, peel, and grape seed-based innovative flour, innovative flour from avocado seeds, special flour from the leaves and stems of various colored cauliflower varieties, and a mixture of kamut and wheat flour added with glucomannan were innovations in consumption flour-based food.